Navigating the nexus: geopolitical, international relations and technical dimensions of US-China cyber strategic competition - Nistha Kumari Singh; Amrita Jash; Yashwanth Nanjappa (Cogent Social Sciences)
The strategic competition between the US and China in cyberspace carries significant consequences for global security, governance and economic stability. This study utilises realist theories such as offensive realism and techno-nationalism to explore how military and technological dynamics influence geopolitical strategic competition. Through comparative and case studies, it examines policy framework, institutional structure (eg USCYBERCOM and China’s ISF/CSF), and cyber incidents, highlighting three interconnected dimensions: geopolitical divergence in the governance model, technical standard setting as a contested area and competing multilateral engagement. The militarisation of cyberspace is evident in military-intelligence competition, cyber espionage, weaponization of cyberspace and corporate competition. Both nations emphasise technological dominance, with the US aiming to maintain its technological supremacy by countering China’s tech ascendancy. The differing global governance norms, namely the US-led free and open internet versus China’s sovereignty-focused model, along with non-state actors heighten the risks of cyber conflicts and arms races. Although the multilateral forums UNGGE, OEWG, etc. seek to establish norms, distrust and competing agendas impede consensus. The study stresses the urgent need for basic international cooperation to mitigate state-sponsored cyber threats. It emphasises that effective governance requires reconciling geopolitical interests with technical and military realities. By dissecting the US-China strategic competition, the primary objective of the research is to analyse the interconnected geopolitical, military and technical aspects of US-China competition in cyberspace.